Spectrographic Observations of Speech of an Ataxic Dysarthric - NP, Nataraja; Nandyal, Indira (Journal of All India Institute of Speech and Hearing)
Speech is a motor act. Speech results from th e fine coordination of various speech muscles. Motor areas in cerebral hemispheres, cerebellum and other lower centres have been considered to be controlling this motor activity. ’Co-ordination of movements and maintenance of balance and muscle tones are dependen t on th e cerebellum and its connections’ (Mysak, 1976).